PENGARUH CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA MADRASAH IBTIDAIYAH NEGERI SURAKARTA TAHUN AJARAN 2025/2026 - Abdul Khaidir Halim; Praptiningsih Praptiningsih; Sulistyowati Sulistyowati (STKIP Pesisir Selatan, 2026)
This study analyzed the implementation level of Contextual Teaching and Learning, mathematics learning outcomes, and its effect on third-grade students’ achievement at MIN Surakarta. It employed a quantitative approach with a correlational design. The population comprised 81 students, all of whom were included through total sampling. CTL implementation data were collected using a questionnaire, while mathematics achievement data were obtained from daily test score documentation. Data were analyzed using descriptive statistics, validity and reliability testing, normality and linearity tests, simple linear regression, and the coefficient of determination. The findings showed that CTL implementation was predominantly in the moderate category, involving 54 students or 66.70%. Mathematics learning outcomes were also predominantly moderate, involving 55 students or 67.90%. Regression analysis produced an F-value of 42.100 with a significance level of 0.000. The correlation coefficient of 0.590 indicated a moderately strong positive relationship. The coefficient of determination of 0.348 showed that CTL explained 34.8% of the variation in mathematics achievement. These findings confirm that contextual learning has a positive and significant effect on students’ mathematics learning outcomes.